Identification of a thermal degradation product of CUMYL‐PEGACLONE and its detection in biological samples. Issue 10 (9th September 2019) - Nash, Christine; Glowacki, Linda; Gerostamoulos, Dimitri; Pigou, Paul; Scott, Timothy; Kostakis, Chris
Abstract: The structural diversity of synthetic cannabinoids makes it a challenging task to have a comprehensive screening method for this class of drugs. The difficulty is increased by the fact that some synthetic cannabinoids undergo thermal decomposition during common routes of administration, such as smoking or vaping. CUMYL‐PEGACLONE is a relatively new synthetic cannabinoid which has a structural variant from most other synthetic cannabinoids: a γ‐carbolinone core. To investigate its thermal stability, CUMYL‐PEGACLONE was heated in an oven at temperatures ranging from 200 to 350 o C, and a major thermal degradation product, N‐pentyl‐γ‐carbolinone, was subsequently identified. Unlike some other synthetic cannabinoids, the thermal degradation product of CUMYL‐PEGACLONE is not one of its known metabolites, nor were any known metabolites detected during the thermal stability experiments. The degradation product was formed in significant amounts at temperatures above 250°C, and has been detected (along with CUMYL‐PEGACLONE) in case samples, including post‐mortem blood and urine, and residue found at a scene. Abstract : Investigation into the thermal stability of CUMYL‐PEGACLONE with the identification of a major thermal degradation product, N‐penyl‐γ‐ carbolinone.